Combining nucleic acid mimics and spectral imaging with fluorescence in situ hybridization for the analysis of the gastric micro-biogeography - Azevedo, Andreia S. (2019)
[Excerpt] Nucleic acid mimics (NAMs)- based assays, such as locked nucleic acid/2′-O- methyl-RNA- fluorescence in vivo hybridization (LNA/2′OMe- FISH), have been developed for the identification and spatial location of Helicobacter pylori directly in the stomach. While H. pylori is considered the main gastric pathogen, there is a diverse range of stomach colonizers that may be associated with disease in the stomach. In this work, giving the enhanced hybridization properties of NAMs, we intend to combine them with FISH and spectral imaging, in one technique. This technique, designated as NAM- CLASI- FISH, will allow the evaluation of the gastric micro- biogeography. [...]